2015
DOI: 10.1186/s13024-015-0021-z
|View full text |Cite
|
Sign up to set email alerts
|

Cholestenoic acid, an endogenous cholesterol metabolite, is a potent γ-secretase modulator

Abstract: BackgroundAmyloid-β (Aβ) 42 has been implicated as the initiating molecule in the pathogenesis of Alzheimer’s disease (AD); thus, therapeutic strategies that target Aβ42 are of great interest. γ-Secretase modulators (GSMs) are small molecules that selectively decrease Aβ42. We have previously reported that many acidic steroids are GSMs with potencies ranging in the low to mid micromolar concentration with 5β-cholanic acid being the most potent steroid identified GSM with half maximal effective concentration (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Previous studies have shown that diverse compounds, referred to as g-secretase inverse modulators, mimic FAD-linked mutations by enhancing Ab 42 generation from the wild-type enzyme (Kukar et al, 2005). In contrast, g-secretase modulators (GSMs) (Weggen et al, 2001), including endogenous metabolites (Jung et al, 2015), enhance protease processivity (Chávez-Gutié rrez et al, 2012;Takeo et al, 2014). However, their mechanisms of action have remained elusive.…”
Section: Exogenous Factors Stabilize or Destabilize G-secretase-substmentioning
confidence: 99%
“…Previous studies have shown that diverse compounds, referred to as g-secretase inverse modulators, mimic FAD-linked mutations by enhancing Ab 42 generation from the wild-type enzyme (Kukar et al, 2005). In contrast, g-secretase modulators (GSMs) (Weggen et al, 2001), including endogenous metabolites (Jung et al, 2015), enhance protease processivity (Chávez-Gutié rrez et al, 2012;Takeo et al, 2014). However, their mechanisms of action have remained elusive.…”
Section: Exogenous Factors Stabilize or Destabilize G-secretase-substmentioning
confidence: 99%
“…In amyloidogenic processing, APP is first cleaved by β-secretase (beta-site APP cleaving enzyme 1, BACE1), releasing a soluble ectodomain called sAPPβ. The remaining membrane associated carboxyl terminal fragment (βCTF) will be further cleaved by γ-secretase within the cell membrane, releasing neurotoxic Aβ peptides and amyloid intracellular domain (AICD; Li et al, 2014 ; Ohki et al, 2014 ; Jung et al, 2015 ; Neumann et al, 2015 ; Sadleir et al, 2015 ; Zhang et al, 2015 ). The exact cleavage site of γ-secretase may vary inside membrane, yielding Aβ peptides with 36–43 amino acids.…”
Section: Introduction Of Alzheimer’s Diseasementioning
confidence: 99%
“…First, the ectodomain of APP is removed by βsecretase and then the membrane-bound C-terminal fragment is cleaved by γ-secretase (71)(72)(73). It is well established that higher cellular levels of cholesterol stimulate β-and γ-secretase activity (74)(75)(76)(77)(78).…”
Section: Several Alzheimer-related Changes Are Triggered In Cetptg Micementioning
confidence: 99%